UPAYA MENINGKATKAN KREATIVITAS ANAK MELALUI TEKNIK USAP ABUR PADA ANAK KELOMPOK A - Dewi Nurhasanah; Lenny Nuraeni (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2022)
Coloring is one of the activities that children like, one of the coloring activities that can be given to children to increase their creativity is coloring using the blurry stroke technique. Wipe blur is a coloring technique using the power of the child's fingers in applying colors that can be used by teachers as a solution to help increase children's creativity. This study aims to assist children in increasing their creativity through the blurry swab technique. This research was conducted at the PAUD Baros Cimahi institution with a qualitative descriptive research method. Data collection was obtained through observation, interviews, and documentation, with the research subjects being group A children and teachers. Analysis of the data used is the reduction and presentation of data as well as drawing conclusions. The results showed that learning using the blurry swab technique can increase creativity in group A children, the creative abilities of children who are already good are three out of five children after participating in coloring activities with the blurry swab technique to increase their creativity and develop according to expectations.